Mesencephalic dopamine neurons are essential for modafinil‐induced arousal. (26th September 2021) - Yang, Yan‐Fei; Dong, Hui; Shen, Yan; Li, Lei; Lazarus, Michael; Qu, Wei‐Min; Huang, Zhi‐Li
Abstract : Background and Purpose: Modafinil is a potent eugeroic (wakefulness‐promoting) drug that is prescribed to treat narcolepsy and has a low incidence of abuse. Although previous studies have shown that modafinil‐induced arousal depends on the dopamine receptors and transporters, the specific part/s of the dopamine transmitter system underlying this mechanism remained unclear. Here, we investigated the role of mesencephalic dopamine neurons in modafinil‐evoked arousal. Experimental Approach: A dopamine indicator (dLight1.1) was employed to detect dopamine changes in the nucleus accumbens (NAc) and dorsal striatum. We specifically lesioned mesencephalic dopamine neurons via diphtheria toxin (DTA) in the dopamine transporter (DAT)‐Cre mice. Then, the sleep–wake states were recorded to evaluate the effect of modafinil on arousal. Finally, the extent of DTA‐induced lesions was determined by immunohistochemistry. Key Results: Modafinil promptly increased dopamine levels in the NAc and dorsal striatum in a dose‐dependent manner. Lesioning of dopamine neurons in the substantia nigra pars compacta (SNc) or ventral tegmental area (VTA) had no significant effects on physiological sleep–wake cycles. Modafinil at 90 mg·kg −1 increased continuous wakefulness for 355 min in control mice. However, these effects were slightly decreased by 6.7% in the SNc‐lesioned mice and were prominently diminished by 32.8% in VTA‐lesioned mice. Furthermore, the modafinil‐induced arousal was completely blocked in the SNc‐VTA‐lesioned mice, whereas lesions of the dorsal raphé nucleus had no effect. Conclusion and Implications: Taken together, our findings indicate that mesencephalic dopamine neurons are essential for modafinil‐induced arousal. Abstract :